A Study of Implicatures in Oscar Films of the 20th Century - Biện Hoàng Thạch (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study investigates maxim violations in three Oscar-winning movies: Gone with the Wind; The Godfather and Hamlet. Grice’s maxims are used in daily conversations to create a comprehensive and purposeful conversation by making a proper answer in response to the message of the counterpart. However, dialogists often either obey or violate Grice’s maxims for various purposes such as concealing a truth, fooling the other speaker, or expressing an implied message. Besides being spotted in many daily conversations, Grice’s maxim violations are also found in movie lines. The researcher uses Gone with the Wind; The Godfather, and Hamlet movie scripts to be investigated to analyze Grice’s maxim violations by the characters’ responses. Three Oscar-winning movies create the possibility of maxim violations on the speakers’ utterances. Therefore, two research questions are formulated to achieve the objectives of the study. The first research question is about which Grice’s maxims are violated in The Godfather, Gone with the Wind, and Hamlet movies. The second one is about the similarities and differences of frequency and linguistic features in creating Maxim violations in The Godfather, Gone with the Wind, and Hamlet films. The finding in this research for the first research question revealed that there were four types of Grice’s maxim were violated in The Godfather, Gone with the Wind and Hamlet movies namely, maxim of Quantity, maxim of Quality, maxim of Relevance, and maxim of Manner. For the second research question, the researcher showed that comparing similarities and differences of frequency and linguistic features in the creating Maxim violations in The Godfather, Gone with the Wind and Hamlet films can add a better understanding of the author’s purposes in creating maxim violations among three films.